(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2025)
Unwanted loneliness is, above all, a feeling and a state of being, in which affective and social aspects are essential. The Royal Academy of Medicine and Surgery of Valladolid organized the series "Unwanted Loneliness," with the support of various institutions and professional associations. It was held in October 2024 at the Academy’s headquarters. The program was structured into the sessions "Unwanted Loneliness: Concept, Individual and Social Responses" and "The Pharmacist and the Physician Facing Unwanted Loneliness." The main conclusion was that to prevent unwanted loneliness, it is essential to foster people’s social networks at different stages of their lives.